2016
DOI: 10.2147/dddt.s106356
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of self-nanoemulsifying drug delivery systems for improved bioavailability of cyclovirobuxine D

Abstract: BackgroundThe main purpose of this research was to design a self-nanoemulsifying drug delivery system (SNEDDS) for improving the bioavailability of cyclovirobuxine D as a poorly water-soluble drug.Materials and methodsSolubility trials, emulsifying studies, and pseudo-ternary phase diagrams were used to screen the SNEDDS formulations. The optimized drug-loaded SNEDDS was prepared at a mass ratio of 3:24:38:38 for cyclovirobuxine D, oleic acid, Solutol SH15, and propylene glycol, respectively. The optimized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Additionally, inhibiting P-glycoprotein (P-gp) efflux is a key property for solubilizers. [47][48][49] TPGS possesses a lipophilic nonpolar head and a hydrophilic tail and would be an ideal surface-active agent to provide a high drug emulsification effect. 50,51 It has been reported that a self-assembled mixture of micelles (TPGS-Icariside IIphospholipid complex) successfully improved the solubility of Icariside II and alleviated efflux in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, inhibiting P-glycoprotein (P-gp) efflux is a key property for solubilizers. [47][48][49] TPGS possesses a lipophilic nonpolar head and a hydrophilic tail and would be an ideal surface-active agent to provide a high drug emulsification effect. 50,51 It has been reported that a self-assembled mixture of micelles (TPGS-Icariside IIphospholipid complex) successfully improved the solubility of Icariside II and alleviated efflux in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The anhydrous SNEDDS samples were visually evaluated for homogeneity and appearance. As a preliminary screening, drug-free SNEDDS formulations were mixed with deionized water at 1:100 w/w ratio to provide fast evaluation of formulation appearance, homogeneity and spontaneity upon aqueous dilution [62][63][64]. Furthermore, SNEDDS formulations were loaded with CUR and PP at ≈80% of their equilibrium solubility and were then subjected to 1:1000 w/w aqueous dilution prior to formulation evaluation.…”
Section: Appearance and Morphologymentioning
confidence: 99%
“…The varying hydrocarbon chain lengths of fatty acids in oil, surface‐active agent and the degree of unsaturation play crucial roles in the spontaneous production of emulsions with smaller DS and stability . Other indices such as EE and DL which were also significant parameters of SEN may be used to evaluate the efficiency of drug loading into nanocarriers . The higher EE (91.51 ± 0.44%) and DL (9.77 ± 0.75%) values of cuminaldehyde entrapment in nanoemulsion indicated a better loading capability.…”
Section: Resultsmentioning
confidence: 99%
“…[76] Other indices such as EE and DL which were also significant parameters of SEN may be used to evaluate the efficiency of drug loading into nanocarriers. [77] The higher EE (91.51 AE 0.44%) and DL (9.77 AE 0.75%) values of cuminaldehyde entrapment in nanoemulsion indicated a better loading capability. These results might be due to the extreme lipophilicity of cuminaldehyde, which may result in the internalisation of cuminaldehyde in the aquaphobic core of the formulation.…”
Section: Characterisation Of Cua-senmentioning
confidence: 92%